(untitled) (Bangabandhu Sheikh Mujib Medical University Journal, 2023)
Background: The surgical management of symptomatic adult Chiari malformation type 1 (CM1) with or without syringomyelia (SM) continues to be a dilemma considering the outcomes. Objectives: The study aimed to compare the clinical outcomes between stealth cranioplasty (SC) and one of the most commonly practiced standard procedures, posterior fossa decompression with duraplasty (PFDD). Clinical outcomes between SC and another procedure posterior fossa decompression (PFD) were also compared. Methods: This comparative cross-sectional study was carried out on 37 males and 16 females symptomatic adult CM1 patients, ranging from 18 to 47 years of age from June 2019 to May 2021. Clinical outcomes were assessed, compared, and analyzed in terms of changes in clinical symptoms and signs, chicago chiari outcome scale (CCOS) score, and occurrence of complications. Results: Of the 53 patients, 23, 19 and 11 underwent SC, PFDD, and PFD, respectively. There were no significant post-operative changes in symptoms and signs among groups except changes in limb weakness between SC and PFDD (P=0.004). Considering average CCOS score, SC performed better only than PFDD (P=0.003), while category-wise SC was better than both PFDD (P=0.004) and PFD (P=0.010). Considering complications, the PFDD group had a significantly higher rate of complications than the SC group (P=0.001), while there was no significant difference in the rate of complications between the PFD and SC groups. Conclusion: SC was found to have better clinical outcomes than the PFDD and PFD groups as a technique. Bangabandhu Sheikh Mujib Medical University Journal 2023;16(1): 08-16